Professional judgement in accounting: contents and conditions of application - Fomina, Olena; Zadniprovsky, Oleksandr; Korol, Svitlana; Romashko, Olha (Business: Theory and Practice, 2022)
The article considers the theoretical prerequisites and regulatory requirements that determine the practical approaches to the application of professional judgment in defining the best way to present reporting information. In the course of the research, the authors took as a basis the regulatory documents on the preparation of financial and integrated reporting, which take a principles-based approach and provide for the use of professional judgment. The authors assumed that the objects of a professional accountant are the facts of economic activity in order to identify, evaluate, recognize and reflect in the accounting and reporting of the company objects of accounting that are significant and of interest to users. The author investigated theoretical bases and practical aspects of application of professional judgment with the purpose of recognition of object and definition of its cost in the course of data collection, their analysis, and formation on their basis of professional judgment. The author has proved the need to adhere to the principle of additionality in finding the maximum complete description of the object and formulating a professional judgement about it. The author proposed a matrix model, which established the correspondence of risk levels and principles of application of professional judgment in accounting valuation and conducted an analysis of the conditions for the use of professional judgment in defining the fair value of financial instruments and inventories. The author considered the influence of uncertainties and corresponding risks in the application of professional judgment on the value of financial instruments and its adjustment in the conditions of unstable markets of countries with economies in transition. The author noted peculiarities of implementation of professional judgment in the process of preparation of financial and integrated reporting and the factors that determine them.